Ennominae II : (Boarmiini, Gnophini, Additions to Previous Volumes). - Müller, Bernd (Geometrid Moths of Europe Ser., 2019)
To purchase all six volumes click here . Final part of The Geometrid Moths of Europe concluding the revision of the European Ennominae moths, covering a total of 181 species plus 21 species of Geometridae found in Europe since publication of previous volumes. Several difficult genera such as Charissa , Psodos , Sciadia , Nychiodes , Selidosema , Peribatodes and the Tephronia complex are covered. Four new species are described, and the fauna is richly illustrated by 1116 specimens in 30 colour plates, 131 genitalia plates and numerous text-figures highlighting diagnostic features. For each species a taxonomic summary, description and diagnosis, distribution map, biology and genetic data are provided. Over 140 taxonomic changes are proposed. A systematic, annotated checklist with synonyms is provided, which summarises the entire Geometridae fauna of Europe (999 species) and adjacent regions.